Antibiotic Resistance Profiling and Microbiota of the Upper Respiratory Tract of Apparently healthy Dogs in Ibadan, South West Nigeria (2017)
Background: Rearing of dogs and other pets has become increasingly popular in modem society. Bacterial flora resides within thè nasal and orai cavities of dogs and when chanced, can be pathogenic. Certain similarities between humans and dogs portends dangerous behavioral habits that could lead to zoonotic disease transmission. This study was aimed at isolation, identification and antibiotic profiling of bacteria from nasal swabs of apparently healthy dogs. The zoonotic risk was also considered. Methodology: A total of 173 nasal swabs were collected from 173 apparently healthy dogs. Structured questionnaires were administered to investigate human behavioral habits. Results: Two hundred and twenty two (222) bacterial isolates were obtained from thè culture with ten (10) potentially pathogenic bacteria in thè order of Escherichia coli (18.5%), Proteus species (17.1%), Staphylococcus aureus (14.0%), Klebsiella species (9.0%), Acinetobacter species (9.0%), coagulase negative Staphylococcus species (7.7%), Pseudomonas species (6.8%), Actinobacter species (6.8%), Citrobacter species (5.9%) and Streptococcus species (5.4%). Overall, thè Gram negative isolates showed resistance to ciprofloxacin (9.3%), sparfloxacin (16.0%),perfloxacin (17.3%), ofloxacin (21.6%), chloramphenicol (34..6%), gentamycin (36.4%), streptomycin (37.%), septrin (49.4%), amoxillin (59.3%), augmentin (62.3%) while thè Gram positive bacteria showed resistance to ciprofloxacin (3.3%), perfloxacin (6.7%), erythromycin (13.3%), streptomycin (21.7%), rocephin (28.3%), septrin (28.3%), gentamycin (36.7%), zinnacef (68.3%), ampiclox (81.7%) and amoxillin (85.0%). Multi-dmg resistance (MDR) to three or more antimicrobials was observed in some of thè isolates. Seventy - seven resistance pattems were observed, 16 in Gram positive and 61 in Gram negative bacteria. Conclusion: This study revealed MDR to two or more antimicrobials in all thè isolates. These can pose antibiotic resistance challenges in situation of primary or secondary canine respiratory infections. Also, this study revealed that 82% of thè dog owners/ lovers had less than 50cm face-to-face contact with these dogs while playing with them, thus increasing their chances of acquiring MDR bacteria from apparently healthy dog